The Impact of the Logo Therapy Approach on the Family Function and Marital Life Satisfaction of Couples with Marital Conflicts - Mohammad Hosein Farahmandi; Abolfazl Bakhshipour; Mahmod Jajarmi (پژوهش‌های کاربردی روانشناختی)
This study was undertaken to investigate the efficacy of the logo therapy approach in improving the family function and marital satisfaction of couples experiencing marital conflicts. The present study employed a quasi-experimental research methodology, which included a two-month follow-up phase, pretest, posttest, and control group design. The follow-up period was conducted over a period of two months. The statistical population of the present study consisted of couples with marital conflicts who visited consultation and wellbeing centers in zone two of Mashhad in the spring and summer of 2021. The purposive sampling method was employed to select 20 couples (40 individuals) who were subsequently randomly assigned to the experimental and control groups (10 couples in the experimental group and 10 in the control group). Ten sessions of logotherapy (90 minutes) were administered to the experimental group over the course of ten weeks. The marital conflict questionnaire (MCQ), family function questionnaire (FFQ), and ENRICH marital satisfaction (EMS) were utilized in this investigation. The SPSS23 software was used to analyze the data obtained from the study using a mixed ANOVA and Bonferroni follow-up test. The results indicated that the logo-therapy approach is effective in improving the family function (F=47.52; Eta=0.55; P<0001,) and marital life satisfaction (F=43.90; Eta=0.53; p<0001) of couples experiencing marital conflicts. According to the findings of the present study, logo therapy can be a highly effective method for enhancing the marital life satisfaction and family function of couples experiencing marital conflicts. This is achieved by utilizing the meaning discovery method, accountability, overcoming despair, increasing life hope, and fostering affective support among the members.